У солнышка в гостях: сказки / [художник О. Крупенкова] - Крупенкова О. (Чтение для малышей, 2008)
Экземпляры: ф.9 (2008) / Инвентарный номер: 52396 / Цена: / Сис.шифр: 82.3(2Рос=Рус)-6 / Авт.знак: У 11 / ГРНТИ: 17.82.93 / ББК: 82.3(2Рос=Рус)-6^VLBC/RL